PENGUATAN PROFIL PELAJAR PANCASILA MELALUI PEMBELAJARAN BERBASIS KETERAMPILAN ABAD KE-21 - Zulaidah, Rizky; Kirani, Sastri; Sari, Cut Kumala (Universitas Negeri Medan, 2025)
The rapid changes of the twenty-first century require education systems to develop students who possess not only academic competence but also strong character and essential life skills. In Indonesia, the Pancasila Student Profile has been introduced through the Merdeka Curriculum as a strategic framework for strengthening character education while responding to global educational demands. This study aims to analyze how twenty-first-century learning approaches contribute to strengthening the Pancasila Student Profile in educational practice. This research employed a qualitative literature review design by analyzing academic journal articles, books, and policy documents related to the Pancasila Student Profile, twenty-first-century learning, and character education. Data were analyzed thematically to identify patterns, key findings, and relationships between contemporary pedagogical approaches and the six dimensions of the Pancasila Student Profile. The results indicate a strong alignment between the Pancasila Student Profile and twenty-first-century competencies, particularly critical thinking, creativity, collaboration, and communication. Project-based learning, problem-based learning, collaborative learning, and the Project for Strengthening the Pancasila Student Profile (P5) were found to be effective in internalizing Pancasila values through contextual and experiential learning. However, challenges such as teacher readiness, limited resources, and infrastructure disparities remain significant obstacles to effective implementation.In conclusion, strengthening the Pancasila Student Profile through twenty-first-century learning requires integrated efforts involving innovative pedagogy, continuous teacher professional development, and systemic institutional support. By combining global competencies with national values, Indonesian education can foster students who are resilient, ethical, and well-prepared to face future challenges.